The second chance boutique : [large type] a novel - Leaman, Louisa (Wheeler Publishing Large Print Hardcover, 2020)
"Francesca Delaney has a knack for matching a bride-to-be with the perfect gown. Her shop, The Whispering Dress, is no ordinary bridal boutique. Every gown is vintage, and the dresses seem to share their stories with Francesca, pointing to which woman needs them next. Fran credits her success to two rules: never covet a dress and never sell a dress that led to a doomed marriage. But then she finds a beautiful 1950s couture floor-length gown, and her talent veers into obsession. The owner, however, would quite like the dark past of the dress to remain hidden forever.."--